ETIKA TANGGUNG JAWAB: Refleksi Filosofis atas Relasionalitas dan Relevansinya dengan Budaya Tuli - Jonathan Adi Wijaya; Fransiskus Xaverius Eko Armada Riyanto (Jurnal Filsafat Indonesia, 2023)
Conscience is one thing that every human being has. The conscience becomes the witness and judge in human actions. Conscience, although it can only be felt by each person, becomes a measure of morality that is able to direct humans to act well and right. This then leads humans to act right in society. As part of society, conscientious people will also consider others in their way of life. Deaf friends are part of a society that cannot be denied. Using literature studies, this article seeks to explore the concept of relationality and then look at its relevance to Deaf culture that occurs in life. Deaf friends certainly have different cultures and rights from humans in general. Deaf culture gradually gained a place in social life. This should be triggered not only by reason, but also by human conscience which is increasingly aware of the existence of equal rights for every human being regardless of the conditions he experiences. Conscience needs to be nurtured and educated in order to be more able to make humans more morally sensitive so that Deaf Culture can really be presented to help Deaf Friends.